2003
DOI: 10.1080/1368282031000121651
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effectiveness of the Hanen Parent Programme and traditional clinic therapy

Abstract: Significant gains in language scores were shown by 71% of the children over 12 months. There were no statistically significant differences in child language scores between the two therapy groups at any assessment point. However, the HPP was twice as intensive (in terms of therapist time) as clinic therapy based on average group size, which has resource implications. CONCLUSIONS. Results suggest that there are parent and child factors that need consideration when choosing an appropriate intervention programme f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
161
0
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(171 citation statements)
references
References 29 publications
6
161
0
4
Order By: Relevance
“…Five of the seven studies targeted children's comprehension in addition to other aspects of language. 169,172,173,175,176 Only two studies targeted children's comprehension specifically.…”
Section: -176mentioning
confidence: 99%
“…Five of the seven studies targeted children's comprehension in addition to other aspects of language. 169,172,173,175,176 Only two studies targeted children's comprehension specifically.…”
Section: -176mentioning
confidence: 99%
“…Ultimately, the parents are empowered to acquire knowledge and skills to support the intervention process. Systematic and committed efforts on this front have resulted in caregivers improving their attitudes vis-à-vis themselves and their children, as well as capacitating them to train and teach their wards (Beckman-Bell, 1981;Tanock and Girolametto, 1992;Baxendale and Hesketh, 2003;Girolametto et al, 2003).…”
Section: Relevance Of Early Intervention To Caregivers Of Children Wimentioning
confidence: 99%
“…The sorts of characteristics which led to the classification of "at risk" included aspects of the family context, such as poverty (for example defined as being below the US Federally defined poverty line), mother"s education or other social, medical and biological risk factors (such as low birth weight, parents who are substance abusers). The remaining children (approximately 200) were reported as having some level of language delay: in three studies, the children were recruited via existing speech language therapy lists (Gibbard et al 2004: , Baxendale and Hesketh 2003: , Girolametto et al 1996. In the remaining studies that included children with an identified language impairment, the children either had identified special educational needs (Crain-Thoreson & Dale 1999) or were identified (or appear to have been identified) in the process of recruitment to the study rather than as part of the local service system.…”
Section: The Childrenmentioning
confidence: 99%
“…Once cannot therefore assume a causative influence from the change in environment to the child"s language. As Baxendale & Hesketh (2003) acknowledge, the direction of influence could indeed be in the opposite direction -i.e. that the changes in the child"s language bring about changes in parent-child interaction.…”
Section: First Stage Findingsmentioning
confidence: 99%
See 1 more Smart Citation